The Influence of Air Fuel Ratio on the Performances and Emissions of a SINJAI-150 Bioethanol Fueled Engines - Ari Kurniawan; Bambang Sudarmanta; Dori Yuvenda (JMES The International Journal of Mechanical Engineering and Sciences, 2018)
In the present work, the effect of variation of air-fuel ratio on performances and emissions SINJAI-150 engine with bioethanol was conducted. Variation of the air-fuel ratio is done by setting the mass flow rate of combustion air using a supercharger. Engine performance was measured using a water brake dynamometer with a variable speed standard from 2000 to 8000 rpm at a fully open throttle condition. The results indicate that the natural intake system produces a relatively rich air-fuel ratio, with an average lambda of 0.68, so that the resulting performance is not maximum. The addition of aspirated 1 and 2 combustion air with the results in the form of average lambda at intervals of 0.8 - 1.1. On the aspirated 2, thermal efficiency increase averaged 50.32%, specific fuel consumption decrease averaged 32.74% and CO and HC emissions reduction average of 7.43 % and 25.77%.